Twelve-Week Daily Gluteal and Hamstring Electrical Stimulation Improves Vascular Structure and Function, Limb Volume, and Sitting Pressure in Spinal Cord Injury: A Pilot Feasibility Study. (17th October 2022) - Barton, Thomas; Low, David A.; Thijssen, Dick H.J.; Romviel, Suzanne; Sloots, Maurits; Smit, Christof A.J.; Janssen, Thomas W.J.
Abstract : Objective: We examined the long-term effects of low-intensity electrical stimulation on (micro)vasculature and sitting pressure of a home-based, wearable electrical stimulation device in a pilot feasibility study. Design: In a cohort observation before-after trial, nine middle-aged male ( n = 8) and female ( n = 1) individuals (48 ± 15 yrs) with American Spinal Injury Association A–C classified chronic (1–24 yrs) spinal cord injury underwent 12 wks of self-administered daily, low-intensity gluteal and hamstring electrical stimulation (50 Hz, 6 hrs [30-min electrical stimulation, 15-min rest]). Common femoral artery diameter and blood blow were determined with ultrasound, skin vascular function during local heating was assessed using Laser-Doppler flowmetry, thigh volume was estimated using leg circumferences and skinfolds, and interface sitting pressure was measured using pressure mapping. Results: Resting common femoral artery diameter increased (0.73 ± 0.20 to 0.79 ± 0.22 cm, P < 0.001) and baseline common femoral artery blood flow increased (0.28 ± 0.12 to 0.40 ± 0.15 l/min, P < 0.002). Gluteal cutaneous vascular conductance showed a time*temperature interaction ( P = 0.01) with higher conductance at 42°C after 12 wks. Ischial peak pressure decreased ( P = 0.003) by 32 ± 23 mm Hg and pressure gradient decreased (23 ± 7 to 16 ± 6 mm Hg, P = 0.007). Thigh volume increased (+19%, P = 0.01). Conclusions: Twelve-week daily home-based gluteal and hamstring electrical stimulation is feasible and effective to improve (micro)vasculature and sitting pressure, and electrical stimulation may have clinical implications for ameliorating pressure ulcers and (micro)vascular complications in spinal cord injury.